A programme-wide training framework to facilitate scientific communication skills development amongst biological sciences Masters students. Issue 4 (3rd July 2016) - Divan, Aysha; Mason, Sam
Abstract : In this article we describe the effectiveness of a programme-wide communication skills training framework incorporated within a one-year biological sciences taught Masters course designed to enhance the competency of students in communicating scientific research principally to a scientific audience. In one class we analysed the numerical marks achieved by students ( N 61) for specific communication assignments completed at the start and at the end of the course. This was complemented by questionnaires administered to students at the beginning and at the end of the course to self-assess their competency and to elicit their views on the usefulness of the training received. We considered three questions: did students' communication skills improve during the course; did the outcomes depend on the place of previous education (UK or non-UK); and how useful did students consider the learning and teaching activities to be? We show that the training improved students' self-reported competency in most of the communication skills considered. Coursework marks for writing literature reviews improved during the course ( p < 0.001). Those marks were marginally associated (that is, approaching statistical significance after Bonferroni correction) with the place of previous education (relatively high in UK students; p = 0.005). Coursework marks for writing research proposals did not change during the course ( p = 0.361) but did depend on place of previous education (relatively high for UK students ( p = 0.001). Although this small study's intriguing results merit further investigation, our initial data supports the use of a programme-wide framework of the type presented here to facilitate communications skills development amongst biological science graduate students.